A new species of Siamites Franz (Coleoptera, Staphylinidae, Scydmaeninae) from Thailand - Jałoszyński, Paweł (Zootaxa, 2013)
A new species of so far monospecific genus Siamites, S. complicatus sp. n., is described. The type specimens were collected in the Krabi Province of Thailand. Morphology of the new species is described and illustrated in details, including male genitalia, and the distribution of Siamites is summarized.